2008
DOI: 10.1021/jp802809c
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Catalytic Adsorption of SO2 on Activated Carbon

Abstract: Catalytic adsorption of SO 2 on activated carbon materials provides an appropriate alternative for the control of low concentration emissions of this air pollutant. The surface complexes formed upon SO 2 adsorption at 30 °C were studied by X-ray photoelectron spectroscopy (XPS) and temperature-programmed desorption (TPD). The effect of the addition of O 2 and the presence of copper as catalyst were studied. Copper assisted the oxygen transfer to the carbon matrix. For the Cu-impregnated carbon sample, the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 26 publications
5
26
0
Order By: Relevance
“…For instance, the contaminant concentration is affected by the scavenging effect of liquid water, adsorption/reaction on carbon within the cell [19,20] and the presence of sulfur on the catalyst carbon support [21]. Therefore, even if a fraction of these effects are reduced by treating the catalyst carbon support or carbon gas diffusion layer to remove the sulfur [22][23][24], the contaminant concentration at the catalyst surface represents an effective value which is smaller than the contaminant concentration in the inlet stream.…”
Section: Model Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the contaminant concentration is affected by the scavenging effect of liquid water, adsorption/reaction on carbon within the cell [19,20] and the presence of sulfur on the catalyst carbon support [21]. Therefore, even if a fraction of these effects are reduced by treating the catalyst carbon support or carbon gas diffusion layer to remove the sulfur [22][23][24], the contaminant concentration at the catalyst surface represents an effective value which is smaller than the contaminant concentration in the inlet stream.…”
Section: Model Assumptionsmentioning
confidence: 99%
“…Eqs. (20) and (21), the initial i value and slope and steady state i value yield 1 , k /k and k X,des estimates:…”
Section: Rate Constants Determinationmentioning
confidence: 99%
“…As for SO 2 removal, Lopez proposed that copper oxides had a catalytic effect toward the transformation of SO 2 into other species [17]. Liu revealed that Fe 2 O 3 reacted with SO 2 resulting in the formation of H 2 SO 4 and Fe 2 (SO 4 ) 3 [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the adsorption temperature ranged from 50 to 90 C. Cu-SAC-9.8 was selected to investigate under the conditions of 2000 ppm SO 2 , 1000 ppm NO, 10% CO 2 , 5% O 2 , and balance N 2 with a total gas flow rate of 400 mL/min. (3) Gas molecules reduced kinetic energies at higher temperature which made adsorption exothermic [17]. As shown in Figure 3a, the 100% removal efficiency of SO 2 was 40, 36, and 32 min at 50, 70, and 90 C, respectively.…”
Section: Effect Of Adsorption Temperaturementioning
confidence: 97%
“…It was reported that added oxygen benefited the adsorption of SO 2 [17,18] and NO [19] on activated carbon materials. Therefore, the effect of oxygen on coadsorption of SO 2 , NO, and CO 2 over Cu-SAC-9.8 was studied under the following condition: adsorption temperature of 50 C and feed gas containing 2000 ppm SO 2 , 1000 ppm NO, 10% CO 2 , 0-5%O 2 , and N 2 as the carrier gas with total gas flow rate of 400 mL/ min.…”
Section: Effect Of Omentioning
confidence: 99%